Analisis Putusan Pengadilan Terhadap Pelaku Inses Dan Pembunuhan 4 Bayi Di Jawa Tengah - Gustira Sabrina Irawan; Fernando Saputra; Asmak Ul Hosnah (Mathematics Education Study Program, 2025)
Incest is one of the behaviors categorized in the Criminal Code as an immoral crime. Incest is usually considered an unethical act and violates social norms because it involves sexual relations with relatives who are too close. murder and even abortion of the baby resulting from inbreeding with the child. Basically, abortion is a prohibited act, Defendant was sentenced to life imprisonment on Wednesday, February 7, 2024. Defendant was found guilty of Article 340 of the Criminal Code, namely premeditated murder and violation of the Child Protection Law. The purpose of this writing stems from the author's curiosity about incest cases and how legal protection in handling these cases. Also to find out how the settlement and punishment of the perpetrators of incest cases and also infanticide that occurred in Central Java.